Pengendalian Risiko Ergonomi Kejadian Gangguan Otot Rangka pada Petugas Laundry RS "X" Palembang Tahun 2024 - Sefrilianita Sefrilianita; Heriziana. Hz (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
The application of ergonomics in the work environment is one of the efforts to ensure the health and safety of an individual or group in carrying out work in a work area that may be at risk of work accidents. Based on data from the Environmental Health and Occupational Safety Installation, musculoskeletal disorders experienced by employees of the "X" Hospital in Palembang in 2022, which stated that 318 employees of the "X" Hospital aged 31-40 years (38.1%), gender (69.2%), length of service <10 years (52.2%), length of service <8 hours (886.2%) with complaints of musculoskeletal disorders in the neck (64.5%), knees/ankles (58.7%), complaints of musculoskeletal disorders (81.4%), mild pain (scale 1-4) 59.0%, mild complaints 49.0%, This study aims to determine the factors related to the incidence of musculoskeletal disorders in Laundry Officers at the "X" Hospital in Palembang in 2024. The subjects of this study were all Laundry Officers at the "X" Hospital in Palembang on July 15-27, 2024. The population and sample in this study were 37 laundry officers. This study uses a quantitative method with analytical observation research and a cross-sectional approach. Furthermore, the collected data was analyzed using the Chi Square Test with a significance level (p value) <0.005. The results of the study were that there were factors related to the incidence of Musculoskeletal Disorders in Laundry Officers with Age (p value 0.005), Gender (p value 0.001), Length of Service (p value 0.001), Work Posture (p value 0.002), and Length of Service (p value 0.000). The conclusion of this study is that there is a relationship between age, gender, length of service, work posture, and length of service with the incidence of Musculoskeletal Disorders in Laundry Officers at RS "X" Palembang in 2024. It is recommended that the Laundry Installation section of RS "X" Palembang conduct a safety briefing to reduce the risk of accidents and provide information on the importance of individual health.